Assessing The Effect of Creative Accounting on Corporate Performance: a Case of Selected Listed Commercial Banks on the Ghana Stock Exchange - Albert Mensah; Ruth Ruby; Daniel Osei; Abdul Wahab Atta Bashiru; Oscar Agyemang Opoku (Pusat Publikasi Nusantara, 2024)
The study examined the effect of creative accounting on the performance of commercial banks listed on the Ghana Stock Exchange. The research design chosen for this study is an ex-post facto research design, which involves examining facts that have already occurred without any interference. The research approach adopted is quantitative, focusing on objective measurements and statistical analysis of data collected through surveys. The study relies on secondary data, specifically financial reports of deposit money banks listed on the Ghana Stock Exchange. The target population includes all the listed commercial banks on the exchange. The sample size consists of 8 out of the 9 commercial banks selected based on their up-to-date financial reports. The data analysis was done with the aid of SPSS software, employing descriptive and inferential statistical techniques such as multiple regression was used to determine the cause and effect relationship among variables. The study found that there was a strong positive link among a bank's size, creative accounting and sales growth and its return on assets and return on equity. Also, SIZE and SG positively affect the profitability (ROA and ROE) of the listed firms on the GSE. However, Creative Accounting negatively affects profitability (ROA and ROE). Therefore, ccommercial banks should be critical regarding on issues or items that they classified under creative accounting. Also, commercial banks should develop strategies to lure many shareholders to invest in the banks in order to improve upon their performance. Moreover, there is urgent need for monitoring companies’ activities in order to raise the quality of financial reporting in Ghana. This can be achieved in determining which accounting manipulation is kept within the limits of legality. Lastly, commercial banks should strengthen their internal control systems in order to deal with issues of creative accounting and misleading financial reports.